THE RELATIONSHIP BETWEEN BODY SIZE AND GROWTH OF AFRICAN CATFISH (CLARIAS GARIEPINUS) (BURCHELL, 1922) FED PRACTICAL DIET - Degani, G; Ben-Zvi, Yigal; Levanon, Dan (Indian Journal of Fisheries, 2011)
The relationship between body size, food utilization and growth of African catfish (Clarias gariepinus)fed on different practical diets was studied.The results show that African catfish can grow on commercial diets found in Israel. The proteinlevel in diet and the sources of protein are the most important parameters in the diet of African catfish.The food utilization and growth are better in smaller fish than in larger fish. The food conversionand protein utilization was better in African catfish fed on diet with high animal protein sources than withplant protein sources.From the economic point of view, this study shows that African catfish requires an expensive diet,similar to that of the trout, and this may influence the possibility of developing a new branch of Africancatfish production in Israel.